1994
DOI: 10.1063/1.468118
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum ultraviolet Fourier transform spectroscopy of the δ(0,0) and β(7,0) bands of NO

Abstract: The combined band oscillator strength of the δ(0,0) and β(7,0) bands of nitric oxide has been measured in absorption by utilizing a vacuum ultraviolet Fourier transform spectrometer to resolve the rotational line profiles. We give accurate rotational line positions of the δ(0,0) and β(7,0) bands, and improved term values up to J=19.5 for the C 2Π(v=0) and J=8.5 for the B 2Π(v=7) levels, measured from the ground state. A deperturbation procedure has been used on the mixed levels, and the calculated molecular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…For v ϭ 0, where the system of term values is overdetermined, most of the E 3 C rotational lines are found to be well within Ϯ0.010 cm Ϫ1 of transition energies calculated from the other three 0 -0 bands, suggesting that the relative errors of the tabulated term values are substantially smaller than 0.010 cm Ϫ1 . In absolute terms, the uncertainties which attach to the term values in Tables 2-4 Table 2 with more recent Fourier transform measurements of the C 4 X 0 -0 line positions (19). The latter were found to be in excellent agreement with measurements by Miescher (25) of photographic spectra recorded at the 10-m VUV spectrograph in Ottawa.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…For v ϭ 0, where the system of term values is overdetermined, most of the E 3 C rotational lines are found to be well within Ϯ0.010 cm Ϫ1 of transition energies calculated from the other three 0 -0 bands, suggesting that the relative errors of the tabulated term values are substantially smaller than 0.010 cm Ϫ1 . In absolute terms, the uncertainties which attach to the term values in Tables 2-4 Table 2 with more recent Fourier transform measurements of the C 4 X 0 -0 line positions (19). The latter were found to be in excellent agreement with measurements by Miescher (25) of photographic spectra recorded at the 10-m VUV spectrograph in Ottawa.…”
Section: Discussionsupporting
confidence: 58%
“…The latter were found to be in excellent agreement with measurements by Miescher (25) of photographic spectra recorded at the 10-m VUV spectrograph in Ottawa. This close coincidence may, however, be fortuitous; an absolute calibration of the Fourier data has not been carried out, and although the photographic measurements are said (19) to have been calibrated with the help of atomic lines, there exists no first-hand evidence to this effect.…”
Section: Discussionmentioning
confidence: 81%
“…Recently Braun et al 17 observed the D 2 ⌺ ϩ -C 2 ⌸ bands in emission with a high-resolution Fourier transform spectrometer in the infrared region. They combined their E→C transition with E→D, D→A, C→A, 16 and also C←X, 18 and they tabulated the term values of the A, D, E, and C states for vϭ0 -2.…”
Section: Introductionmentioning
confidence: 99%
“…Published integrated cross sections 7-9 measured at insufficient spectral resolution differ, in some cases by more than 50%, possibly indicating saturation. 10 To overcome the problems of insufficient resolution line-by-line measurements of the absorption cross sections of the ␦͑0,0͒ and ␤͑7,0͒ bands of NO in the region 195 nm were performed by Murray et al 11 Using the Fourier transform ͑FT͒ spectrometers at Imperial College, London ͑IC͒ NO data were procured with a resolution of 0.06 cm Ϫ1 . This work achieved a signal to noise ͑S/N͒ ratio of 25 as measured at the continuum level in the transmission spectrum but this was not sufficient to determine the photoabsorption cross sections of weaker lines accurately.…”
Section: Introductionmentioning
confidence: 99%